Gym Members' Perceptions of Supplement Use: Insights and Trends - Akbar, Rakha Athaya Putra; Suprianta, Eka; Yosika, Ghana Firsta (Universitas Negeri Surabaya, 2025)
Purpose: This research was undertaken with the aim of determining gym members' perceptions of supplements, identifying the frequency of supplement use, and pinpointing the sources of information about supplements. These objectives were crucial in understanding the current landscape of supplement usage among gym members. Materials and Methods: This research, uniquely conducted at various gyms in Pontianak, namely Roxy GYM, KGYM Ilham, and Bali GYM, involved 156 respondents. The study used a quantitative descriptive research method, a robust approach to data collection. Data were collected using a questionnaire containing statements and answers, which was distributed via a Google Form accessed through a QR/barcode, a modern and efficient data collection method. Result: The findings of this study are significant. They indicate that gym members have an average 'positive' perception of supplements. The highest frequency of supplement use was for 'Protein Milk,' primarily consumed according to the time of need. Most respondents obtained information about supplements from the Internet and social media platforms like Facebook, Instagram, and YouTube, highlighting the influence of online sources on supplement consumption decisions. Conclusion: nformation from online sources significantly influences gym members' decisions to consume supplements. However, it's clear from this research that there's a pressing need for more accurate and reliable information about supplements to be disseminated to the broader community. This is crucial to ensure that gym members, and indeed all supplement users, can make informed decisions about their health and performance.